Format Baru Transformasi Pendidikan Islam - Samsuddin Samsuddin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2012)
The role and contribution of Islam as a religion in the process of education in this country is both clear and remarkable. The contribution is so significant that many have believed that the Islamic system of education in the country has become what can be called a sub-culture within the national system of education. This paper tries to expose this in the context of the goal, the development and the core of education in Islam. The paper argues that the Islamic system of education is based on the vision of the Qur`an concerning man, his knowledge and attitude. For Islam, education is about sharpening man?s mind and softening his heart. It is this premise that underlines the whole argument of the paper. The paper further shows that this vision is in a total line with the objectives and goals of our national education. The paper then speaks of what it calls the ?new nationalistic form of Islamic education? in which the religious and national values are integrated. This new model of education is not only idealistic but also transformative and innovative in the context of Indonesia and is relevant vis-?-vis the demands of modernity.